Hubungan Self Efficacy Dengan Student Engagement Pada Siswa di MAN 2 Bener Meriah - Erda Sulyani; Salamiah Sari Dewi (Universitas Medan Area, 2022)
This study aims to determine whether there is a correlation between self-efficacy and student engagement in students at Madrasah Aliyah Negeri 2 Bener Meriah. This study uses quantitative research methods. The number of samples in this study were 53 students. This study was compiled based on the Likert scale method using a self-efficacy scale, namely level, strength and generality. and the student engagement scale, namely behavior engagement, emotional engagement and cognitive engagement. The data analysis technique in this study used the Pearson product moment correlation technique. The results of data analysis show a correlation coefficient where r_xy = 0.998 with a significant p = 0.000 0.050. This means that the proposed hypothesis is accepted. It is assumed that the more positive self-efficacy for students, the higher student engagement will be, or vice versa, the more negative self-efficacy for students, the lower the level of student engagement for students at the school. From the results of this analysis, it is known that the self-efficacy of students at MAN 2 Bener Meriah is high (empirical mean = 109.53 hypothetical mean = 77.5). The coefficient of determination was found to be r^2 = 0.997. This shows that self-efficacy contributes to student engagement 99.7%